Program Edukasi dan Pemberdayaan Masyarakat: Pemanfaatan Kelor (Moringa Oleifera) sebagai Sumber Nutrisi untuk Pencegahan Stunting dan Kekurangan Gizi di Posyandu Melati Kelurahan Wonosari Kecamatan Ngaliyan - Aripin, Ipin; Ismunadi, Ali; Vitta Yaumul Hikmawati; Norita Agustina Subagyo; Estining Titah Kinasih (INCOME: Indonesian Journal of Community Service and Engagement, 2025)
Stunting is a symptom of chronic malnutrition that results in impaired growth and development in children. One of the economical nutritional sources in the effort to prevent stunting is through the utilization of the moringa plant. This plant is proven to have good nutritional content as an alternative or supplement in stunting prevention efforts. The objective of this Community Service Program (CSP) is to empower the community, especially the partner group of cadres and members of the Melati Integrated Health Post (Posyandu) in Wonosari Village, Ngaliyan District, Semarang. The Participatory Action Research (PAR) method, through socialization and training activities, was used in the implementation of this CSP. The target participants in this program were 12 cadres of the Melati Posyandu in Wonosari Village, Ngaliyan District, Semarang, with a total of 50 target children, 20 of whom were indicated to be malnourished. The results of this CSP show an increase in nutritional and stunting knowledge among the Melati Posyandu cadres. Furthermore, the participants also experienced an improvement in their skills in processing and cultivating the moringa plant as an affordable and accessible alternative nutritional source. Based on this CSP, the utilization of moringa as a nutritional supplement to overcome malnutrition and stunting can be recommended.